‘The rates of pre-hospital over-triage and the reasons behind them in a Cape Town setting' - McAlpine, David (Division of General Surgery, 2022)
Introduction: Inappropriate dispatch of urgent ambulances by call centre personnel causes an unnecessary drain on existing resources. How often these urgent dispatches are inappropriate has not been evaluated in any lower middle income countries, nor have factors been assessed that contribute to these decisions. Problem: The study aims to establish rates of pre-hospital over-triage in Cape Town, South Africa and to assess the call centre factors around these decision-making processes. Methods: This was a retrospective study examining a single calendar month of all urgent ("lights and sirens") ambulance dispatches made from a large public sector ambulance call centre in Cape Town. On-scene, the ambulance field crew assessed these patients using the South African Triage Score (SATS) and these assessments were correlated with the prioritization of these dispatches by the call centre to determine which patients were 'over-triaged' by the call-taker. Contributory factors were also analysed and included time of day, nature of presenting complaint; and call-taker training and experience - all of which may have affected rates of over-triage. Results: In the course of one month in 2017, 4169 urgent calls were assessed: of these 2701 were over-triaged (58.48%). Over-triage was similar between day (58.02%) and night (59.11%). The most regularly over-triaged complaint was obstetric & gynaecological (84.87%) followed by motor vehicle accidents (65.70%); the lowest rate was for cardiac call-outs (47.12%). We reviewed the 38 highest workload call-takers, and found subtle, but non-statistically significant, trends towards higher over-triage rates with higher levels of training (ILS 62.16%, no medical training 59.42%; p=0.67), more years as a call-taker (< 2 years 59.32%, > 5 years 60.23%; p=0.93) and more years working in the field (0 years 59.36%, > 5 years 63.66%; p=0.31). Conclusion: Rates of pre-hospital over-triage in Cape Town are marginally lower than those described internationally. The nature of the complaint had a strong impact on these rates, notably trauma and gynaecological issues. More experienced call-takers may tend to over-triage more frequently, however the small sample size made these findings uncertain. These findings do however suggest the potential for improvement for better efficiency without compromising patient safety.